2014
DOI: 10.3892/ijmm.2014.1785
|View full text |Cite
|
Sign up to set email alerts
|

Chronic exposure to simulated space conditions predominantly affects cytoskeleton remodeling and oxidative stress response in mouse fetal fibroblasts

Abstract: Abstract. microgravity and cosmic rays as found in space are difficult to recreate on earth. However, ground-based models exist to simulate space flight experiments. In the present study, an experimental model was utilized to monitor gene expression changes in fetal skin fibroblasts of murine origin. Cells were continuously subjected for 65 h to a low dose (55 mSv) of ionizing radiation (IR), comprising a mixture of high-linear energy transfer (LET) neutrons and low-LET gamma-rays, and/or simulated microgravit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 37 publications
2
35
0
Order By: Relevance
“…These devices can equalize the gravity vector and cancel the effect of gravity, thereby simulating μG. However, there are two major limitations associated with this approach: (i) it is necessary to stop rotation during irradiation as the sample was exposed to radiation outside the incubator after or before rotation with a RWV [183][184][185][186][187][188] and (ii) nonuniformity of dose flatness in the irradiation area occurs because of chronical irradiation of a rotating sample with a RPM [189,190]. To address these problems, we have developed a system of simultaneous irradiation in simulated-μG (SSS) using 3D clinostat [191,192].…”
Section: Combined Biological Effectsmentioning
confidence: 99%
“…These devices can equalize the gravity vector and cancel the effect of gravity, thereby simulating μG. However, there are two major limitations associated with this approach: (i) it is necessary to stop rotation during irradiation as the sample was exposed to radiation outside the incubator after or before rotation with a RWV [183][184][185][186][187][188] and (ii) nonuniformity of dose flatness in the irradiation area occurs because of chronical irradiation of a rotating sample with a RPM [189,190]. To address these problems, we have developed a system of simultaneous irradiation in simulated-μG (SSS) using 3D clinostat [191,192].…”
Section: Combined Biological Effectsmentioning
confidence: 99%
“…Ideally, cells should be exposed to μg and different radiation qualities at the same time. However, only a limited number of studies have yet been performed in which cells are simultaneously exposed to both these physical space stressors (Beck et al 2014;Pani et al 2016;Fernandez-Gonzalo et al 2017). In a recent study simulated μg was found to increase particle radiation-induced apoptosis in B lymphoblast cells (Dang et al 2014).…”
Section: The Combined Effects Of μG and Radiationmentioning
confidence: 99%
“…There is an issue with these previous studies in that it was necessary to stop the rotation during the irradiation. Another issue was that the sample on the 3D clinostat in an incubator was chronically irradiated using neutrons from californium-252 (Beck et al, 2014;Pani et al, 2016) (Fig. 1B).…”
Section: Introductionmentioning
confidence: 99%